(untitled) (Bodhi Path, 2024)
The word perfection means the state or feeling of being complete. That is, which is completely filled, in which no space or place is left empty. Therefore, by reducing craving, a man moves towards perfection. Just as a man characterized by perfection is completely satisfied and content in every way. In this sequence, Siddhartha also attained perfection as a result of continuous practice of many births and was called Buddha. His birth, enlightenment after birth and Mahaparinirvana became symbols of perfection by being perfect. (पूर्णता शब्द का अर्थ पूर्ण होने की अवस्था या भाव है | अर्थात् जो पूरी तरह से भरा हुआ हो, जिसमें कोई अवकाश या स्थान रिक्त न रह गया हो | अतः तृष्णा को घटाकर ही मनुष्य पूर्णता की ओर अगसर होता है | जिस प्रकार पूर्णता से प्रतिपादित मनुष्य सभी तरह से तृप्त और सन्तुष्ट होता है | इसी क्रम में सिद्धार्थ ने भी अनेक जन्मों की अनवरत साधाना के फलस्वरूप पूर्णत्व प्राप्त किया और वे बुद्ध कहलाये | उनका जन्म, जन्म के पश्चात् सम्बोधि एवं महापरिनिर्वाण में परिपूर्ण होकर पूर्णता के प्रतीक बने |)